Analisis Permasalahan Dan Kebijakan Penanggulangan Sampah di Daerah Pajajaran Kota Bandung - Ageng S. Kanda; Citra Puspita Sari (Institut Nalanda, 2024)
A common problem in the management of garbage is the low awareness of the public to avoid dumping at the bottom of the river. As it becomes increasingly difficult to find a decent dumping place and inadequate transportation of the waste, the people dump the waste on the banks. Moreover, the lack of means and facilities to support the dumping causes the people to discourage dumping to the rivers and other sources. The research method I chose was the questionnaire method. Share survey questions and interviews with respondents. Research instruments are lifting and individual interviews. The information collected using this method is often quantitative. Quantitative research is research that requires large amounts of data. This is because the population of quantitative research participants is very varied. The conclusion from the discussion is that the results before educating the importance of preserving the environment and carrying out the cleaning program of the river cytepus by after doing so, that the rating of the respondents has increased to positive that means that this activity is effective in its implementation for 1 week in the month of November 2023, after the rainy season comes once there is a minimum of flooding and river does not flood into the road. In order to prevent flooding, it is important to carry out sanitary work in the community's environment and river transport, manage the garbage properly, carry out the disposal of organic and inorganic waste, give education on the importance of keeping the environment and the river clean.